Liver fat metabolism of broilers regulated by Bacillus amyloliquefaciens TL via stimulating IGF-1 secretion and regulating the IGF signaling pathway - Chen, Pinpin; Li, Shijie; Zhou, Zutao; Wang, Xu; Shi, Deshi; Li, Zili; Li, Xiaowen; Xiao, Yuncai (Frontiers in Microbiology, 2022)
Bacillus amyloliquefaciens TL (B.A-TL) is well-known for its capability of promoting protein synthesis and lipid metabolism, in particular, the abdominal fat deposition in broilers. However, the underlying molecular mechanism remains unclear. In our study, the regulations of lipid metabolism of broilers by B.A-TL were explored both in vivo and in vitro. The metabolites of B.A-TL were used to simulate in vitro the effect of B.A-TL on liver metabolism based on the chicken hepatocellular carcinoma cell line (i.e., LMH cells). The effects of B.A-TL on lipid metabolism by regulating insulin/IGF signaling pathways were investigated by applying the signal pathway inhibitors in vitro. The results showed that the B.A-TL metabolites enhanced hepatic lipid synthesis and stimulated the secretion of IGF-1. The liver transcriptome analysis revealed the significantly upregulated expressions of four genes (SI, AMY2A, PCK1, and FASN) in the B.A-TL treatment group, mainly involved in carbohydrate digestion and absorption as well as biomacromolecule metabolism, with a particularly prominent effect on fatty acid synthase (FASN). Results of cellular assays showed that B.A-TL metabolites were involved in the insulin/IGF signaling pathway, regulating the expressions of lipid metabolism genes (e.g., FASN, ACCα, LPIN, and ACOX) and the FASN protein, ultimately regulating the lipid metabolism via the IGF/PI3K/FASN pathway in broilers.